Naskh dalam Sunnah dan Implikasinya terhadap Hukum dan Tafsir Al-Qur'an - Muhammad Abbas (ANWARUL, 2026)
Although the concept of nashk (nasakh) has been a topic of inquiry in Islamic jurisprudence, research that specifically examines its implications within the Sunnah and its influence on Qur’anic tafsīr remains relatively limited. This study aimed to analyze the role of nashk in the Sunnah and its implications for legal determination and Qur’anic tafsīr. A qualitative approach was employed using a library study design focused on analysis of the Qur’an, hadith, and relevant classical and contemporary tafsīr works. The findings show that nashk is an important component in understanding the development of Islamic law because it reflects the flexibility and adaptive capacity of Islamic jurisprudence to changing social and historical contexts. In addition, nashk plays a significant role in Qur’anic interpretation by influencing both the evolving legal principles and the methodologies applied by scholars in understanding religious texts. This study contributes to a broader understanding of the application of nashk and offers new insights into its dynamic impact on legal theory and Qur’anic tafsīr. The study concludes that nashk is essential for maintaining the integrity of Islamic law while enabling its adjustment to contemporary challenges, and it encourages scholars to consider its implications in the context of modern legal issues and Qur’anic interpretation.